Hoaks Di Media Sosial Dalam Perspektif Hadis - Roudatus Solihah; Mus’idul Millah; Siti Nuralisah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Fake news or what is commonly called hoax is behavior that is strictly prohibited by Islam, and this behavior of hoaxes existed long before the development of technology, especially in today's information that moves so fast on social networks that it is difficult for users to distinguish valid information from hoax. This study uses a type of qualitative research, namely the hadith thematic method. The formal object of this research is the understanding and prohibition of hoax behavior which are grouped based on hadith themes. Meanwhile, the material object in this study is the spread of information that moves so fast on social media networks. The discussion in this study explains the prohibition of disseminating information that is not true. The conclusion of this study is that it is important for every individual to become a smart consumer of information, check the correctness of the information before sharing it, and contribute to the dissemination of accurate and useful information in the digital world.